In Arcadia: Landscape filming in a toxic wasteland Game engine affordances and post-game narratives - Corrado Morgana (University of Edinburgh, 2008)
Videogames, whether immersive simulations or abstract puzzlers, impose their own set of internal logics upon the player. If the player decides to transgress or subvert the rules or normal behaviour without directly affecting the software system itself through modification or hacking, these same internal logics still affect the player or ‘subvertors’ behaviour; the videogame has its own set of affordances, the properties that an artefact or system has that influence interaction.